1988
DOI: 10.4319/lo.1988.33.4_part_2.0725
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microbial dynamics in marine and freshwater sediments: Contrasts in anaerobic carbon catabolism

Abstract: The microbiota of freshwater and marine sediments serve similar roles in carbon degradation and nutrient regeneration. However, because of differences in the chemical environment between freshwater and marine systems, distinct physiological groups of bacteria dominate terminal carbon catabolism in each system. In general, the distribution and rates of microbial activities within a sediment are determined by availability of electron acceptors for respiration and metabolizable organic substrates.Sulfate ion is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
322
1
2

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(329 citation statements)
references
References 45 publications
4
322
1
2
Order By: Relevance
“…Sulfide oxidation -As noted earlier, the sulfur cycle always dominates the pathways of anaerobic decomposition when sulfate is abundant (see Capone and Kiene 1988). Consequently, the oxidation of sulfides and other reduced products of the sulfur cycle is much more important than methane oxidation in marine systems.…”
Section: Deep-sea Conditionsmentioning
confidence: 90%
See 2 more Smart Citations
“…Sulfide oxidation -As noted earlier, the sulfur cycle always dominates the pathways of anaerobic decomposition when sulfate is abundant (see Capone and Kiene 1988). Consequently, the oxidation of sulfides and other reduced products of the sulfur cycle is much more important than methane oxidation in marine systems.…”
Section: Deep-sea Conditionsmentioning
confidence: 90%
“…Capone and Kiene 1988;Jorgensen 1983;Fenchel and Blackburn 1979). Briefly, organic matter is fermented by one group of microbes, and then another group uses the fermentation products of hydrogen, fatty acids, and acetate either in sulfate reduction or in methanogenesis.…”
Section: Deep-sea Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical profiles in pore water of organic-rich sediments indicate that various microbes use a series of electron acceptors during the remineralization of organic matter in the order of decreasing chemical potential, and methanogenesis accounts for the last stage of the microbial respiration. In stratified lakes developing an anoxic hypolimnion, methanogenesis and sulfate reduction are key terminal processes in anaerobic carbon remineralization (Capone and Kiene 1988). One of the factors controlling the end products of microbial decomposition is the competition between methanogenic microorganisms and sulfate-reducing bacteria (SRB) for common substrates such as hydrogen and acetate.…”
mentioning
confidence: 99%
“…Concomitantly, sea level rise will also influence the supply of specific TEAs, such as SO 4 2À , with uncertain effects on mineralization. It is already well established that the availability of TEAs affects the last (terminal) step of anaerobic decomposition (Capone and Kiene, 1988;Reddy and D'Angelo, 1994;D'Angelo and Reddy, 1999;Megonigal et al, 2004) by acting through interspecific competition for electron donors (acetate and H 2 ). Indeed, previous work has demonstrated that sea level rise can lead to a shift of electron flow from methanogens to the competitively superior sulfate reducers (Neubauer et al, 2005;Weston et al, 2006).…”
Section: Introductionmentioning
confidence: 99%